Longitudinal Association of Carotid Plaque Presence and Intima-Media Thickness With Depressive Symptoms in the Elderly: The Three-City Study. Issue 5 (May 2015) - Prugger, Christof; Godin, Ophelia; Perier, Marie-Cécile; Ritchie, Karen; Helmer, Catherine; Empana, Jean-Philippe; Tzourio, Christophe; Dufouil, Carole
Abstract : Objective—: To investigate prospectively whether subclinical vascular disease is associated with future depressive symptoms in the elderly. Approach and Results—: A multicenter cohort of community-dwelling individuals aged 65 to 85 years was examined for carotid plaque presence and common carotid artery intima-media thickness at baseline and followed up after 2, 4, 7, and 10 years. At baseline and follow-up examinations, depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (CES-D). High level of depressive symptoms was defined as a CES-D score >16 in men and >22 in women. Among 4125 participants (58% women) at baseline, men more frequently showed carotid plaque presence and had higher mean common carotid artery intima-media thickness than women. After adjustment for major cardiovascular risk factors, carotid plaque presence was associated with a higher CES-D score at the 10-year follow-up in men (+1.46; 95% confidence interval, 0.71–2.20; P <0.001), but not in women. When restricting analyses to individuals without cardiovascular disease at baseline, carotid plaque presence increased the likelihood of high level of depressive symptoms at follow-up examinations in men (odds ratio, 1.47; 95% confidence interval, 1.06–2.05; P =0.022), but not in women. One SD increase in log-transformed common carotid artery intima-media thickness was associated with a higher CES-D score at the 10-year follow-up in women (+0.55; 95% confidence interval, 0.16–0.95; P =0.006) and men (+0.40; 95% confidence interval, 0.02–0.78; P =0.037). Common carotid artery intima-media thickness did not increase the likelihood of high level of depressive symptoms at follow-up in both sexes. Conclusions—: Subclinical vascular disease is associated with the progression of depressive symptoms in elderly men and women and the occurrence of high level of depressive symptoms in elderly men. Abstract : Supplemental Digital Content is available in the text.